Durability properties of cleaner cement mortar with by-products of tire recycling. (10th March 2019) - Gheni, Ahmed A.; Alghazali, Hayder H.; ElGawady, Mohamed A.; Myers, John J.; Feys, Dimitri
Abstract: This study investigates using rubber-fiber powder (RFP), which is by-products of tire recycling, as an additive in a cement-based mortar. Five different RFP ratios of 5, 10, 15, 20, and 25% were used in this study as an additive filler side by side with reducing the cement content by the same amount. In addition to the fresh properties and the heat of hydration, the physical characterization of the rubberized mixtures including the compressive, and flexural strength the hardened density, absorption, and air voids were investigated. The results were compared to those where the cement content was reduced without adding the RFP as well as a reference mortar mixture having 0% RFP. To evaluate the new rubberized mortar as a reinforcement corrosion protector, the bulk and surface electrical resistivity, the accelerated carbon dioxide penetration, and the rapid chloride ion penetration tests were determined. Although there was a reduction in some of the mechanical characterizations, this study revealed that the recycled rubber-fiber powder could be used in the mortar as an additive to provide more corrosion resistance and less heat of hydration compared to the control mixture. Adding the RFP lowered and delayed the peak temperature for the heat of hydration compared to reducing the cement content only. From the durability side, mortar mixtures with up to 20% RFP showed an improved reinforcement corrosion resistance by increasing both bulk and surface electrical resistivity. Highlights: By-products of tire recycling (RFP) can be used as an additive to cement mortar. By-products of tire recycling lowered and delayed the peak heat of hydration. Adding up to 20% of RFP to cement mortar improved reinforcement corrosion resistance. Volume of permeable air voids has a direct impact on the steel corrosion resistance.